Two-dimensional boron nitride allotrope Irida-B12N12 with 3-6-8 membered rings and wide-bandgap semiconducting properties - Marcelo L. Pereira; Djardiel da S. Gomes; Kleuton A. L. Lima; Georges D. A. Nze; Fábio L. L. Mendonça; Luiz A. Ribeiro (Scientific Reports)
Abstract We present a novel two-dimensional (2D) boron nitride allotrope, Irida- $$\hbox {B}_{{12}}$$ B 12 $$\hbox {N}_{{12}}$$ N 12 (Ir-BN), analogous to the all-carbon Irida-Graphene (Ir-G). The predicted structure of Ir-BN consists of alternating boron and nitrogen atoms, forming three distinct lattices with 3-, 6-, and 8-membered ring patterns. First-principles calculations based on density functional theory (DFT) formalism and ab initio molecular dynamics (AIMD) simulations were performed to investigate its structural, mechanical, electronic, and optical properties. The Ir-BN lattices exhibit good dynamical and thermal stability, supporting their viability as new 2D materials. Substantial anisotropy is observed in the mechanical properties, with in-plane stiffness ranging from 16 to 142 N/m, depending on the direction, and bulk moduli between 78 and 95 N/m. The electronic structure analysis reveals that Ir-BN is a wide-bandgap semiconductor, with band gaps ranging from 2.4 to 3.2 eV. The material shows optical activity particularly in the visible and ultraviolet regions.